2018
DOI: 10.1186/s13068-018-1294-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lignin fractions isolated from different biomass sources on cellulose oxidation by fungal lytic polysaccharide monooxygenases

Abstract: BackgroundLytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes that oxidatively cleave recalcitrant lignocellulose in the presence of oxygen or hydrogen peroxide as co-substrate and a reducing agent as electron donor. One of the possible systems that provide electrons to the LPMOs active site and promote the polysaccharide degradation involves the mediation of phenolic agents, such as lignin, low-molecular-weight lignin-derived compounds and other plant phenols. In the present work, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 54 publications
(76 reference statements)
1
41
0
Order By: Relevance
“…Numerous reports have shown that process samples of lignocellulose refining support LPMO activity [7, 30, 31, 3638]. The positive effect on LPMO activity has been assigned to the electron donating ability of lignin and lignin-derived, mostly phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have shown that process samples of lignocellulose refining support LPMO activity [7, 30, 31, 3638]. The positive effect on LPMO activity has been assigned to the electron donating ability of lignin and lignin-derived, mostly phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…According to the originally proposed mechanism [5], LPMOs require O 2 as a co-substrate and delivery of two electrons from an external electron donor per glycosidic bond cleavage [27, 28]. A number of different compounds can support LPMOs with electrons [29], including phenolic compounds [7, 30–35] or lignin and its fragments [7, 31, 3638], which are both expected to be present in liquid fractions emerging during thermochemical pretreatment of biomass [3, 3945].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Harris et al observed that the boosting effect of an LPMO on cellulase action required the presence of other compounds in the biomass, most likely lignin-derived [134]. In retrospect, it is clear that these observations relate to the reducing power that is present in biomass but not in model cellulosic substrates such as Avicel [134,143,247]. In an important study, Eibinger et al used confocal microscopy to show that a cellulolytic LPMO from N. crassa primarily acts on surface-exposed crystalline areas of the cellulose and that LPMO treatment promoted adsorption of a CBH, TrCel7A, to these crystalline regions, resulting in more efficient hydrolysis of these cellulose crystals [96].…”
Section: Co-operativity Between Enzyme Componentsmentioning
confidence: 99%
“…The spruce and birch lignins used in this study, which were isolated by the hybrid organosolv-steam explosion method, contained a very low amount of ash (<0.1 wt.%), as well as minimal carbohydrate impurities, i.e., hemicellulose (<2 wt.%) and cellulose (<1 wt.%) [34,35]. Their molecular weights were also in the range of previously reported values for similar organosolv-type lignins, with a relatively narrow molecular mass distribution as evidenced by the low polydispersity index (PDI) values [22,85,87,90,91]. Table 1.…”
Section: Lignin Characteristicsmentioning
confidence: 79%